The integrated aircraft routing problem with optional flights and delay considerations. (October 2018) - Kenan, Nabil; Jebali, Aida; Diabat, Ali
Highlights: We integrate flight scheduling and fleet assignment with aircraft routing. We simultaneously consider these three decisions when the demand is stochastic. We consider the problem with propagated delay and deadhead flights. We develop three column generation-based algorithms to solve the problem. Results show that our algorithms can reach optimality gaps of less than 0.1%. Abstract: In this paper, we integrate flight scheduling, fleet assignment, and aircraft routing decisions, which are the most prominent decisions in airline planning, while considering the stochasticity of the demand. In addition, optional flights, delays and deadhead flights are considered as they are crucial elements that significantly affect airline profits. Due to the complexity of the formulated problem, three different column generation-based algorithms are developed. The results show that our algorithms can solve the problem in a fraction of the time a commercial solver takes with an optimality gap of less than 0.1%.